Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/da.22093
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Grief Symptoms in Anxiety Disorders: Prevalence and Associated Impairment

Abstract: Background Previous research has identified high rates of comorbid anxiety disorders among individuals presenting with primary CG. In the present study, we examined the prevalence of comorbid CG in bereaved primary anxiety disorder (AD) patients compared to bereaved healthy controls. We also examined the impairment associated with comorbid CG in AD. Methods Participants were 242 bereaved adults (mean (SD) age = 41.5 (13.1), 44.2% women) with a primary AD diagnosis, including generalized anxiety disorder (GAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 37 publications
4
26
0
1
Order By: Relevance
“…We also reported that individuals with CG exhibited higher levels of lifetime panic-spectrum symptoms, than otherwise healthy bereaved individuals, even after controlling for current PD diagnosis (Bui et al, 2013). Correspondingly, we found in a recent study that 18% of individuals with a primary diagnosis of PD, who lost a loved one at least six months prior, screened positive for CG compared to less than 1% in individuals without any current DSM-IV psychiatric disorders (Marques et al, 2013), and approximately 7% prevalence in the general population (Kersting et al, 2011). …”
Section: Introductionmentioning
confidence: 71%
“…We also reported that individuals with CG exhibited higher levels of lifetime panic-spectrum symptoms, than otherwise healthy bereaved individuals, even after controlling for current PD diagnosis (Bui et al, 2013). Correspondingly, we found in a recent study that 18% of individuals with a primary diagnosis of PD, who lost a loved one at least six months prior, screened positive for CG compared to less than 1% in individuals without any current DSM-IV psychiatric disorders (Marques et al, 2013), and approximately 7% prevalence in the general population (Kersting et al, 2011). …”
Section: Introductionmentioning
confidence: 71%
“…Individuals with anxiety disorders exhibit elevated rates of CG (Marques et al, in press). Conversely, adults with CG exhibit high rates of comorbid anxiety disorders (Simon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Participants rated the frequency of each symptom on a 5-point Likert scale with total scores raging from 0 to 76. Consistent with previous research (Marques et al, 2013; Shear et al, 2005), threshold CG was defined as ≥ 30.…”
Section: Methodsmentioning
confidence: 88%